The THE EFFECT OF CLOVER OIL ON THE BACK PAIN OF PREGNANT WOMEN: THE EFFECT OF CLOVER OIL ON THE BACK PAIN OF PREGNANT WOMEN - Desi Br Sembiring (LPPM STIKes Buleleng, 2025)
Introduction: Lower back pain often makes mothers feel disturbed by the pain that arises due to lower back pain. The pain experienced by every third trimester pregnant woman who experiences lower back pain is different. Ideally, complaints of lower back pain during pregnancy occur due to anatomical changes in the body due to the increase in the size of the fetus in the uterus. Method: This research uses a Quasi Experimental design with a pre test and post test approach. The population is third trimester pregnant women in the Medan Tuntungan health center working area. The sample was 11 pregnant women in the second trimester using a numerical rating scale instrument. Data analysis was carried out using the Paired t-test statistical test to test differences before and after intervention. Result: The intervention resulted in back pain in pregnant women with an average value of 4.82 and after the intervention was given, it showed a decrease in back pain in pregnant women with an average value of 2.55. Conclusion: There is an effect of giving clove oil on back pain in pregnant women with a statistical test result of p-value 0.000 (<0.05), meaning there is a significant reduction in the intervention that has been carried out.